Preliminary Characterization of Co-processed Excipients of Okra (Abelmoschus esculentus) Mucilage and Pregelatinized Potato Starch (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Okra mucilage is highly viscous with good binding properties in tablets. Pregelatinized starches have significantly improved flow properties but produce tablets of poor mechanical strength.Objective: Preliminary evaluation of co-processed excipients of Okra mucilage and pregelatinized potato starch as directly-compressible excipients.Methods: Polymers were characterized for morphology (SEM), crystallinity (FT-IR) and flow properties.  Co-processed excipients were developed with Okra mucilage and pregelatinized potato starch at different ratios of starch: mucilage (95:5, 90:10, 85:15, 80:20, 70:30), using the co-fusion method. The flow, packing and compaction properties of the co-processed excipients were evaluated using density measurements, angle of repose, angle of internal friction, Kawakita model, consolidation index (C) and consolidation rate (K).Results: Larger agglomerates of the co-processed excipients indicated formation of a new polymer. FT-IR spectra showed retention of all the major peaks of individual polymers. Okra mucilage imparted swelling while starch improved flow in the co-processed excipients (Hausner’s ratio 1.12-1.20).  Values from Kawakita plots revealed cohesiveness and compressibility were imparted to the co-processed excipients (a = 0.300–0.329; b = 0.078–0.361) suggesting good compactibility. Consolidation index and rate were observed to increase with Okra mucilage content, implying improved rate of packing as well as enhanced flow (C = 0.566-1.389; K = 0.123-0.424). The batch containing starch: mucilage 70:30 gave the best properties of good flow, cohesiveness and compactibility, essential parameters required in directly-compressible excipients.Conclusion: The co-processed excipients of Okra mucilage and pregelatinized potato starch could therefore be used as excipients for direct compression in tablet formulations